Effect of Zembrin® and four of its alkaloid constituents on electric excitability of the rat hippocampus. (15th September 2018) - Dimpfel, Wilfried; Franklin, Richard; Gericke, Nigel; Schombert, Leonie
Summary: Ethnopharmacological relevance: Sceletium tortuosum ( Mesembryanthemaceae ), a succulent plant indigenous to South Africa. is consumed in the form of teas, decoctions and tinctures and is sometimes smoked and used as snuff. In recent years, Sceletium has received a great deal of commercial interest for relieving stress in healthy people, and for treating a broad range of psychological, psychiatric and inflammatory conditions. Material and methods: The whole extract (Zembrin®) was tested ex vivo in the hippocampus slice preparation after one week of daily oral administration of 5 and 10 mg/kg. Four alkaloids – mesembrine, mesembranol, mesembrenol and mesembrenone – were tested directly in vitro. All four were also tested in the presence of different glutamate receptor agonists. Results: Zembrin® ex vivo as well as all alkaloids in vitro attenuated the amplitude of the population spike during electric stimulation as single shock as well as theta burst stimulation. Only Mesembranol and Mesembrenol having a hydroxyl group at position C6 instead of carbonyl group as in mesembrine and mesembrenone acted by attenuation of AMPA receptor mediated transmission as documented for the whole extract. Discussion: The current experimental series revealed a new physiological effect of Zembrin ® on the electric activity of the hippocampus. Attenuation of AMPA mediated transmission has been related to successful adjunctive treatment of epileptic patients. Administered doses of 5 and 10 mg/kg are in line with a dosage of 50 mg/subject as tested clinically. Conclusion: We have discovered a new structure activity relationship for Sceletium alkaloids. Since attenuation of AMPA mediated transmission has been related to successful adjunctive treatment of epileptic patients), Mesembrenol and Mesembranol may serve as new chemical leads for the development of new drugs for the treatment of epilepsy. Graphical abstract: Effects of 5 mg/kg of Zembrin ® in the presence of glutamate receptor agonists (x-axis). Results from slices as obtained during theta burst stimulation. Data are given as mean ± S.E.M. Amplitude of the signal is given as voltage in mV (y-axis). Dark graphs represent the action of glutamate receptor agonists alone (reference data from an earlier experimental series), grey graphs show the population spike amplitudes measured in slices from animals pre-treated with 5 mg/kg Zembrin ® . Statistical significance of p < 0.01 is marked by stars.